Partnering With VA Stakeholders to Develop a Comprehensive Patient Safety Data Display: Lessons Learned From the Field. (March 2016) - Chen, Qi; Shin, Marlena H.; Chan, Jeffrey A.; Sullivan, Jennifer L.; Borzecki, Ann M.; Shwartz, Michael; Rivard, Peter E.; Hatoun, Jonathan; Rosen, Amy K.
Health care systems are increasingly burdened by the large numbers of safety measures currently being reported. Within the Veterans Administration (VA), most safety reporting occurs within organizational silos, with little involvement by the frontline users of these measures. To provide a more integrated picture of patient safety, the study team partnered with multiple VA stakeholders and engaged potential frontline users at 2 hospitals to develop a Guiding Patient Safety (GPS) tool. The GPS is currently in its fourth generation; once approval is obtained from senior leadership, implementation will begin. Stakeholders were enthusiastic about the GPS's user-friendly format, comprehensive content, and potential utility for improving safety. These findings suggest that stakeholder engagement is a critical first step in the development of tools that will more likely be used by frontline users. Policy makers and researchers may consider adopting this innovative partnered-research model in developing future national initiatives to deliver meaningful programs to frontline users.